Comparative Analysis of Altman Z-Score and J-UK Model Accuracy in Predicting Financial Distress during the Covid-19 Pandemic (Study on Manufacturing Companies listed on the Indonesia Stock Exchange) - Rahmawati, Annisa Pratiwi; Juliarto, Agung (Diponegoro Journal of Accounting, 2024)
This study aims to analyze the comparison of the predictive ability of Altman Z-Score and J-UK model. There are five financial ratios used in the Altman Z-Score model, namely capital to total assets, retained earnings to total assets, earnings before interest and taxes to total assets, market value equity to book value of total debt, and sales to total assets. Meanwhile, the J-UK model is a modification of the Altman Z-Score model with an additional ratio in the form of cash flow from operations to total liabilities. The research sample used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020 and 2021. There are 201 non-financial distress companies and 101 financial distress companies. Hypothesis testing used in this study is a classification matrix. From the results of the classification matrix, it was found that the predictive ability of the Altman Z-Score was 78.1% and the ability of the J-UK model was 78.1%. Therefore, the results showed that the Altman Z-Score and J-UK models have the same financial distress prediction ability in manufacturing companies in Indonesia.